EXPLORING THE REASONS FOR SEEKING PROSTHODONTICS TREATMENT FROM UNQUALIFIED PRACTITIONERS IN PESHAWAR - Asma; Wagma; Sobia Anwar; Awais Hassan Khan (Pakistan Oral & Dental Journal, 2024)
Objectives: The study focused on investigating the reasons why participants visited quacks for prosthodontics therapy, what factors motivated them to do so, and how satisfied they were with both quacks and qualified dentists.Methodology: This cross-sectional study was conducted between June 2023 and October 2023. A total of 110 patients, aged between 45 and 65 years, who had visited quacks for prosthodontics procedures in the past six months, were interviewed at three different well-equipped clinics in Peshawar. The collected data on their motivations/reasons for seeking treatments from quacks were collected through a pre-designed and pre-tested questionnaire and analyzed through basic statistical methods.Results: Female to male ratio was 1: 1.75 in the current study. The pattern of awareness and reasons for visits to the quacks was observed same for both genders (P> 0.05). The primary reason for visiting the quack was often a lack of awareness. Other factors included economic considerations, proximity to one’s residence, the convenience of a single appointment, and referrals. The level of education and age of the participants did not have a significant effect on the scenario (P > 0.05). Many of the participants expressed dissatisfaction with the treatment they received from the quacks and stated that the services offered by qualified dentists were better, safer, and less painful.Conclusions: Awareness programs for altering the attitudes of the community are mandatory. Furthermore, it is essential to implement strictly established laws to stop the illegal practice of quacks. In addition, doctors are deployed to rural areas for practice.
Keywords: Prosthodontics Patients; Reasons for visits quacks; District Peshawar